TO STUDY THE PLANNING AND DESIGNING OF PIPE DESTRIBUTION NETWORK - Mr. Y. B. Survase, Dr. M. G. Deshmukh, Tank Gaurav, Kusumade Harshal, Misal Mandar, Padavale Amar, Bagal Ganesh, Thorbole Mahesh (International Journal of Innovations in Engineering Research and Technology, 2022)
66.67% of farmland relies on pandharpur and groundwater sources for irrigation, and global warming and climate change often lead to drought conditions. Sewerage distribution network systems have various drawbacks such as uneconomical water loss and maintenance costs in the long run. This shortcoming can be overcome with the latest alternative pipe distribution network system.Pipe distribution network systems have advantages over traditional methods. The study area is the Kudari Medium Irrigation Project in the Krishna River basin in the Satara district of Maharashtra. This study focuses on the design of some PDNs in the Kudari Medium Irrigation Project and the hydraulic modeling of irrigation networks designed for effective water management systems. To minimize this problem, this research contributes through an approach to the planning and design of pipe distribution networks used for irrigation purposes. Pipe distribution network (PDN) for irrigation is one of the best solutions to significantly improve design and actual OPE (efficiency of the entire facility). Pipe Distribution Network (PDN) is a technique for irrigating command areas through a network of HDPE pipes under gravity rather than open channels. This document describes the need for a PDN system, the benefits and scope of PDN, the basic requirements for PDN implementation, general PDN installation guidelines, and PDN planning and design principles. This treatise also discusses the magical improvement of OPE in irrigation projects with the introduction of PDN. This paper compares the project efficiency improvement rate and other parameters of the illustrated project in the village of Dapawadi in Satara, Maharashtra.